Exploring the role of palmitoylation in sepsis: mechanistic insights and future perspectives - Susu Cao; Wenyan Xiao; Sinong Pan; Tianfeng Hua; Min Yang (Molecular Medicine)
Abstract Background The palmitoylation system is intricate, multidimensional, and plays a crucial role in various inflammatory and immune-related disorders. Palmitoylation controls protein stability, cargo sorting, signal transmission, as well as cell differentiation and death. Notably, a growing body of studies has highlighted its participation in inflammatory processes, either directly or indirectly, indicating its broad and complex involvement in the development of sepsis. Understanding the mechanisms underlying palmitoylation is essential for advancing research on sepsis. We began this review with a brief summary of research related to sepsis progression. Second, we went over recent studies on palmitoylation. Third, we compiled and described palmitoylation-related alterations in vital molecules or biological processes involved in sepsis. Lastly, we outlined the promising features of palmitoylation and proposed a hopeful outlook for future research in sepsis.